Mastery of information technology and strengthening collaboration between editors and marketing: Local media strategies for surviving during Covid-19 pandemic - Anas Syahirul Alim; Andre Noevi Rahmanto; Sri Hastjarjo (Universitas Negeri Yogyakarta, 2023)
There was a global pandemic with the emergence of the Covid-19 virus from 2019 until 2022. The pandemic affected all aspects of life, including the press/media world. Media crews had been facing tough challenges during the midst of a pandemic situation. Journalists were required to do work in the field to produce quality content. The business division was required to continue to generate revenue for the company in order to produce quality journalistic works. On the other hand, they had to protect themselves from contracting the plague while carrying out their duties with all the challenges and risks. Since the arrival of the Covid-19 pandemic, local media revenue has continued to fall. Newspaper sales dwindled, advertising sales slumped, events could not run. While operational costs were not reduced but instead increased. Local media also had to struggle with their own strategies to survive. Mastery of information technology to strengthen collaboration between the editorial department and the marketing department was the key to succeed